Relationship of Body Mass Index, Leg Muscle Strength, and Muscle Sleeve Strength against The Speed of Karate Punch (Journal of Physical Education and Sports, 2018)
The purpose of this study was to analyze the significant relationship between body mass index on the speed of punching Gyaku-Tsuki, to analyze the significant relationship between leg muscle strength to the speed of punching Gyaku-Tsuki, and to analyze the significant relationship between arm muscle strength to the speed of punching Gyaku-Tsuki. This research is non-experimental quantitative research. The research design used is a correlation design. In this study, researchers used total sampling. The variable is divided into two independent variables, body mass index, leg muscle strength, and arm muscle strength. While the dependent variable is the speed of punching Gyaku-Tsuki. Techniques data collection uses tests and measurements. Data analysis used simple regression and multiple regression. The results of this study indicate that body mass index only contributes 2.8%, leg muscle strength is only 4%, arm muscle strength is only 2.9%, and body mass index, leg muscle strength, and arm muscle strength only 4.8%. The conclusions of this study are body mass index factor, leg muscle strength, arm muscle strength does not have a significant relationship to the speed of punching Gyaku-Tsuki either alone or together.